2020
DOI: 10.3390/molecules25143306
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Polylactic Acid Biocomposite Films Reinforced with Cellulose Nanofibrils

Abstract: Polylactic acid (PLA) is one of the most promising biodegradable and recyclable thermoplastic biopolymer derived from renewable feedstock. Nanocellulose reinforced PLA biocomposites have received increasing attention in academic and industrial communities. In the present study, cellulose nanofibrils (CNFs) was liberated by combined enzymatic pretreatment and high-pressure homogenization, and then subsequently incorporated into the PLA matrix to synthesize PLA/CNF biocomposite films via solution casting and mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
(44 reference statements)
5
37
0
Order By: Relevance
“…CNF has been previously reported to affect not only on the mechanical properties of the polymer matrix but also the thermal properties. [ 46, 54 ] The result of the DTG confirmed the earlier reported literature. [ 23, 55 ] Figure 8(A)‐(D) showed the differential scanning calorimetry of the neat PLA and the composite with increased CNF loading.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…CNF has been previously reported to affect not only on the mechanical properties of the polymer matrix but also the thermal properties. [ 46, 54 ] The result of the DTG confirmed the earlier reported literature. [ 23, 55 ] Figure 8(A)‐(D) showed the differential scanning calorimetry of the neat PLA and the composite with increased CNF loading.…”
Section: Resultssupporting
confidence: 86%
“…The dispersion of CNF resulted in no agglomeration and therefore result in inter-facial and intra-facial interaction of the polymer mix as seen in the surface morphology ( Figure 3) and the schematic drawing ( Figure 5) of the PLA and CNF interaction. [46] The values of the tensile strength in this study are similar to those reported by Abdul Khani et al [47] on PLA/modified CNF. However, Their study solves the agglomeration challenge between PLA and CNF with chemical acetylation of CNF as against this present study on supercritical preparation of CNF.…”
Section: Mechanical Propertiessupporting
confidence: 90%
See 3 more Smart Citations